An enhanced quasicrystalline Ti1.4V0.6Ni alloy electrode modified by uniformly covered RGO for nickel metal hydride battery. (December 2020) - Ding, Nan; Liu, Wanqiang; Sun, Lianshan; Lin, Jin; Liang, Fei; Wang, Limin
Abstract: Herein, we provided a facile route to coat a flat and uniformly covered reduced graphene oxide (RGO) film on Ti1.4 V0.6 Ni quasicrystal alloy electrode surface by electrodeposition of graphene oxide and subsequent reduction with HI vapor. Raman spectrum showed HI has a better reduced effect than electrochemical reduction. The RGO coated alloy electrode exhibited a higher discharge capacity of 290.3 mA h g −1 and 23.8% higher capacity retention than the bare one after 50 cycles for the RGO layer effectively forbidding the direct contact of electrode and electrolyte. Moreover, Ti1.4 V0.6 Ni quasicrystal alloy with RGO coating exhibited faster hydrogen uptake kinetics by initial activation curve of gaseous hydrogen storage measurement and higher maximum hydrogen storage performance of 1.66 wt% than the bare Ti1.4 V0.6 Ni alloy. Thus, the enhanced properties of RGO as a multifunctional layer for Ti1.4 V0.6 Ni quasicrystal alloy were proved which could be achieved by a facile route. Highlights: RGO coating layer is prepared by electro-deposition and subsequent reduction. Raman spectra measurement proves the degree of reduction of RGO enhanced by HI. Cycle stability of Ti1.4 V0.6 Ni is enhanced by RGO for its anti-corrosion ability.